2019
DOI: 10.2320/matertrans.me201911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forging Temperature on Microstructure Evolution and Tensile Properties of Ti-17 Alloys

Abstract: In this study, the microstructure, tensile strength, elongation, and reduction of area of near-¢ Ti alloys (Ti-17) were investigated after being subjected to solution and aging treatments. Ti-17 was forged at temperatures between 700 and 850°C followed by air cooling. Then, the forged Ti-17 was subjected to solution treatment at 800°C for 4 h followed by water quenching and aging treatment at 620°C for 8 h followed by air cooling. Tensile tests were performed at room temperature, 450°C, and 600°C. The change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The microstructures of the samples forged at various forging temperature are shown in Fig. 4 [11]. It was found that the forging temperature affected only the morphology of GB alpha phase; that is, the granular shape alpha phase was observed along grain boundaries for the samples forged at 700 and 750 ˚C.…”
Section: Microstructurementioning
confidence: 96%
See 2 more Smart Citations
“…The microstructures of the samples forged at various forging temperature are shown in Fig. 4 [11]. It was found that the forging temperature affected only the morphology of GB alpha phase; that is, the granular shape alpha phase was observed along grain boundaries for the samples forged at 700 and 750 ˚C.…”
Section: Microstructurementioning
confidence: 96%
“…The microstructure evolution was clarified by observation of the microstructure of as-forged, solution-treated and aged samples [11]. It was found that the beta phase exhibited and the alpha phase formed at only grain boundary during forging.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Next, the forged specimens were solution treated and aged (STAed), their microstructure evolution was investigated, and a prediction model for STA was established [6]. The tensile strength and fatigue life of the specimens forged using the 1500 t press and STAed were tested to understand the microstructural factors that control the mechanical properties, and a prediction model for tensile strength was established [7,8]. To apply the prediction model to the 1500 t forging press, coefficients of friction and thermal transfer were determined by comparing experiments conducted using the hot forging emulating system and Finite Element Method (FEM) [9].…”
Section: National Projects On Titaniummentioning
confidence: 99%
“…In previous studies, we investigated the dependence of the microstructure evolution of Ti-17 alloy on the forging conditions, along with the corresponding tensile properties [25,26]. Cylindrical Ti-17 ingots with a diameter of 134 mm and height of 192 mm were isothermally forged using a 1500 t forging press and then air-cooled.…”
Section: Introductionmentioning
confidence: 99%